Comparative analysis of galectin-1, galectin-3, and galectin-8 signatures in normal and choriocarcinoma trophoblast cell lines - Jovanović Krivokuća Milica; Legner Janko; Ćujić Danica; Vilotić Aleksandra; Grubiša Ivana; Vićovac Ljiljana; Bojić-Trbojević Žanka (Archives of Biological Sciences)
Galectins are found in the placenta during both normal and pathological conditions. Specifically, galectins -1, -3, and -8 have been identified in extravillous trophoblast cells, with galectins -1, and -3 playing notable roles in trophoblast cell function. Altered expression profiles of galectins are linked to various cancers. This study explores the expression and localization of galectins -1, -3, and -8 in a normal extravillous HTR-8/SVneo cell line and two choriocarcinoma cell lines, JAR and JEG-3. Expression levels of these galectins at both mRNA and protein levels were evaluated using PCR, qPCR, and Western blotting, while their cellular localization and distribution were assessed through immunocytochemistry, subcellular fractionation, and Western blotting. Galectins -1, -3, and -8 were expressed at lower levels in JAR and JEG-3 cells compared to HTR-8/SVneo cells. Additionally, different splice variants of galectin-8 were detected across all cell lines. Galectin-1 was predominantly localized at the plasma membrane. Notable differences in galectin-3 localization and distribution were observed between HTR-8/SVneo cells and choriocarcinoma cells. These findings highlight variations in the expression, staining patterns, and subcellular distribution of galectins -1, -3, and -8, suggesting their potential involvement in the pathology of choriocarcinoma.